Design of Objective IT Strategy, Risk Driver and Risk Control: Design of Objective IT Strategy, Risk Driver and Risk Control - Tati Ernawati (Competitive, 2015)
Information technology (IT) played a central role in the productivity of IT industry intensively. IT provides organizations with the flexibility to redesign processes and create a high-performing organizational design. IT strategy objective used to focus on developing specific business capabilities. Right IT strategic can bring the corporate achieve vision, mission and objectives have been established. Risk must be managed effectively to maximize the effectiveness of its use and that the associated risks of the implemented technology can be mitigated. This paper present a case study in risk management at Food and Beverage Corporate related to achievement of corporate goals . The Research method used is Strategic Objectives at Risk (SOAR) which consists of four stages. The results of this study is proposed strategic Objective IT Map in related Risk driver, risk control include its metric.